2019
DOI: 10.1002/jcp.28948
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of human serum of patients with non‐small‐cell lung cancer reveals proteins as diagnostic biomarker candidates

Abstract: Non-small-cell lung carcinomas (NSCLC) is the most common type of lung cancer and it has a poor prognosis, because overall survival after 5 years is 20-25% for all stages.Thus, it is extremely important to increase the survival rate in the early stages NSCLC by focusing on novel screening tests of cancer identifying specific biomarkers expression associated with a more accurate tumor staging and patient prognosis. In this study, we focused our attention on quantitative proteomics of three heavily glycosylated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…Presently, proteomics-based liquid biopsy guided cancer treatment is still in early stage [19]. Studies have shown that the potential value of screen cancer biomarkers from blood via proteomics [19,25,26]. Our results suggested anlotinib-induced the alteration of plasma protein levels from responders may be used as alternative biomarkers.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Presently, proteomics-based liquid biopsy guided cancer treatment is still in early stage [19]. Studies have shown that the potential value of screen cancer biomarkers from blood via proteomics [19,25,26]. Our results suggested anlotinib-induced the alteration of plasma protein levels from responders may be used as alternative biomarkers.…”
Section: Discussionmentioning
confidence: 72%
“…Proteomic technology has been used in biomedical research widely since its development [17][18][19]. Ying Jiang et al found that proteomic could identify novel therapeutics targets for hepatocellular carcinoma [20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations